QSAR modeling of isoquinoline derivatives having AKR1C3 inhibitory activity: Lead optimization - Papichettypalle Gopinath, Dwivedi Ashish ranjan, Beda Durgaprasad, Karkara Bidhuhusan, Pathuri Raghuveer, Godela RamReddy, Kasula Ramalingeswara Rao, Dontireddy Ravisankara Reddy, Sibala Subramanyam (Journal of Applied Pharmaceutical Science, 2024)
Aldo-keto reductase 1C3 is a promising drug target for castration-resistant prostate cancer. In the present study, quantitative structure-activity relationship studies were carried out by QSARINS software on 3-(3, 4-dihydroisoquinolin-2(1H)-yl sulfonyl) benzoic acid derivatives having AKR1C3 inhibitory activity. The developed Quantitative Structure-activity relationship (QSAR) model suggests that the descriptors play key roles and are extremely helpful in predicting bioactivity. The best model shows validated statistical values, and residual information predicts the obtained model is robust, stable, and can be utilized to the extent of a novel series of isoquinoline derivatives.
Keywords: Prostate cancer, AKR1C3, QSARINS, MoRSE